Clerks : 'over the counter' culture and youth cinema - Templeton, Peter, 1986- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Clerks (1994) was born of and appeals to a specific youth subculture, with the multimedia 'View Askewniverse' developing out of the film's initial release. This study of Kevin Smith's debut film breaks new ground by exploring how Clerks sits at the intersection of political and cultural trends relevant to alternative youth cultures in the early 1990s. Drawing on existing texts and movements such as Richard Linklater's Slacker (1991), Douglas Coupland's novel Generation X: Tales for an Accelerated Culture and alternative rock subcultures that had developed during and since the 1980s, the film presents a comedic take on working as a young person in 1990s America in a manner that was praised for its authenticity. Filmed on a miniscule budget, the roughness of the film's aesthetic, combined with a hard rock soundtrack comprised of mostly independent bands, convinced many that it could speak for young Americans, much more than polished, corporate Hollywood productions. At a time when young men were pessimistic about their economic prospects and their role in society was changing, Clerks provides a vivid representation of them caught in the pinch of this unsettling historical moment"--
'Insubordination rules': Clerks and the counterculture of the 1990s -- 'A job that makes a difference': youth and employment -- 'Who closed the store to play hockey?': work and leisure -- 'I still get free Gatorate, right?": Clerks, youth and consumption -- 'Any balls down there?': Clerks, slacker masculinity and sexaulity.
"Routledge Focus" -- front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Clerks (Motion picture); Generation X -- In motion pictures; Labor in motion pictures; SOCIAL SCIENCE / Media Studies